Evaluasi Geometrik Konstruksi Jalan pada Tanjakan Ir Sutami PJR Bandar Lampung Menggunakan Pengukuran Topografi - Meraty Ramadhini; Akbar Wahyu Nugraha; Dandy Ardian Dani Saputro; Safridatul ‘Audah (LPPM Politeknik Aceh Selatan, 2024)
In general, steep inclines are made winding for the reason that they reduce the energy required to reach the same height. The slope of the incline will be gentler with curves so it is easier to climb, because the car does not have enough power to climb steep slopes so the road is made winding. Based on accident data from the KNKT, the highest number of accidents that occurred on the PJR Bandar Lampung ramp was 21 incidents in a year. Geometric road on an incline. The winding and narrow condition of PJR Bandar Lampung makes it difficult for vehicles to pass this section of road. The aim of this research is to carry out geometric analysis and evaluation of roads on the PJR Bandar Lampung incline based on Road Geometric Design Guidelines Number 13/P/BM/2021 using topographic measurements. The results of the geometric evaluation of the road were suitable for corner 4 with a superelevation below 6% and with a minimum radius from a speed of 20 km/h to 50 km/h, while the results were not suitable for the average ideal lane width of 3 m. maximum superelevation is 10.01%, maximum slope is 9.81% and critical slope length is 9.33%. So the road geometry does not comply with Road Geometric Design Guidelines Number 13/P/BM/2021.